Tipologi Dayah: Pondok Pesantren - Risna Purwanti (Lembaga Pengembangan Kinerja Dosen, 2024)
This research aims to determine the typology of Islamic boarding schools as Islamic educational institutions with a focus on Islamic boarding schools regarding the typology of Islamic educational institutions which have distinctive religious characteristics that are different from other Islamic boarding schools. This Islamic boarding school is not only a place to gain religious knowledge, but also a place for character formation, skill development, and integration of Islamic values ​​in everyday life. This research uses a qualitative approach with interview and observation techniques to collect data. The resulting data was then analyzed using content analysis techniques. The research results show that Islamic boarding schools or Dayah have different characteristics from modern Islamic boarding schools. Islamic boarding schools or Dayah have unique characteristics in curriculum development, teaching methods and institutional management.